Pengelolaan Kandang Dan Pengaruhnya Terhadap Produktivitas Ternak Babi - Fitriani; Wiyadi (Jurnal Ilmu Peternakan Indonesia, 2025)
Good barn management is one of the important factors in supporting pig productivity. This study aims to analyze the impact of barn management on pig productivity, including growth, health, and reproduction. The research method used was direct observation at pig farms implementing various barn management systems, such as ventilation, sanitation, feeding, and temperature management. The results of the study show that optimal barn management can improve the quality of life of pigs, accelerate growth, and reduce mortality and disease rates. On the other hand, poor barn management can reduce productivity and increase the risk of infections. Therefore, proper barn management plays a significant role in the efficiency and success of pig farming.